2022
DOI: 10.1002/mabi.202200150
|View full text |Cite
|
Sign up to set email alerts
|

A Straightforward Approach towards Antibacterial and Anti‐Inflammatory Multifunctional Nanofiber Membranes with Sustained Drug Release Profiles

Abstract: Preventing bacterial infection and controlling the inflammatory response occupy important positions in wound treatment. Although loading wound dressings with antibacterial or anti-inflammatory drugs/molecules is an effective approach to address these issues, simultaneous sustained release of these drugs remains challenging. Herein, hydrophilic polyhexamethylene guanidine hydrochloride (PHGC) and hydrophobic indomethacin (Indo) are loaded in hydrophilic polyvinyl alcohol (PVA) and hydrophobic polycaprolactone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The results demonstrated enhanced cell proliferation and adhesion, indicating the biocompatibility of the dressing. Similarly, Wang et al [ 59 ]evaluated the cell viability of PCL/PVA hydrogel dressings and observed improved cell attachment and viability compared to traditional wound dressings. In a study that was published in 2021, hybrid nanofibers made of PCL/PVA and biopolymers were created for use in wound dressings.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated enhanced cell proliferation and adhesion, indicating the biocompatibility of the dressing. Similarly, Wang et al [ 59 ]evaluated the cell viability of PCL/PVA hydrogel dressings and observed improved cell attachment and viability compared to traditional wound dressings. In a study that was published in 2021, hybrid nanofibers made of PCL/PVA and biopolymers were created for use in wound dressings.…”
Section: Resultsmentioning
confidence: 99%
“…Pro-inflammatory cytokine interleukin-6 (IL-6) involved multiple processes, such as immune response, inflammation, and hematopoiesis during wound reparation. [69] The IL-6 provides an early favorable wound healing response through the activation of epithelial repair mechanisms; however, paradoxically, IL-6 also promotes inflammation by activating the signal transducer and activator of transcription 3 (STAT3). [70,71] Vascular endothelial growth factor (VEGF) plays a central role in mediating the process of angiogenesis or new blood vessel formation, and the formation of blood vessels could facilitate wound repair by providing sufficient nutrients to the damaged tissue.…”
Section: Histomorphological and Immunohistochemical Analysesmentioning
confidence: 99%
“…14 Indomethacin (Indo) is a nonsteroidal anti-inflammatory drug that can inhibit the secretion of prostaglandins (PGs), reduce pain, and inflammation. 15 Bioactive dressings have garnered a lot of attention recently because of their unique evolution from merely covering and protecting wounds to multifunctional ones that are capable of addressing several issues along with acceleration of healing. 16 One of the bioactive dressings is polymer nanofibers with unique properties for local treatment of wounds due to their extraordinary drug loading capacity, high surface-to-volume ratio, porous microstructure, high gas permeability, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, their direct use is limited by their high molecular mass, short half-life, and hydrophilicity, etc . Indomethacin (Indo) is a nonsteroidal anti-inflammatory drug that can inhibit the secretion of prostaglandins (PGs), reduce pain, and inflammation …”
Section: Introductionmentioning
confidence: 99%